The effects of short-term hypergravity on Caenorhabditis elegans. (August 2016) - Saldanha, Jenifer N.; Pandey, Santosh; Powell-Coffman, Jo Anne
Abstract: As we seek to recognize the opportunities of advanced aerospace technologies and spaceflight, it is increasingly important to understand the impacts of hypergravity, defined as gravitational forces greater than those present on the earth's surface. The nematode Caenorhabditis elegans has been established as a powerful model to study the effects of altered gravity regimens and has displayed remarkable resilience to space travel. In this study, we investigate the effects of short-term and defined hypergravity exposure on C. elegans motility, brood size, pharyngeal pumping rates, and lifespan. The results from this study advance our understanding of the effects of shorter durations of exposure to increased gravitational forces on C. elegans, and also contribute to the growing body of literature on the impacts of altered gravity regimens on earth's life forms.